15. Chat and Instant Messaging Systems (synchronous): Report 3/ 3 - Ludwig, Brian; Poscente, Krista; Baggaley, Jon; Fahy, Patrick J. (International Review of Research in Open and Distributed Learning, 2002)
A further set of four text-based instant messaging (IM) products was evaluated: AT&T Anywhere, Parachat, Sonork, and Yahoo Messenger, all available at no cost. Yahoo Messenger was judged to be the most effective of the three products for use by distance education (DE) teachers and students, being compatible with most common operating systems and accommodating up to 50 chat room participants. Yahoo Messenger also possesses integrated audio and video capabilities. AT&T Anywhere is an efficient product, which supports Windows-based operating systems only. Parachat (Basic version) is a basic, browser accessed chat board without instant messaging (IM) capabilities.